2009
DOI: 10.1111/j.1469-0691.2009.02974.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation of zygomycosis

Abstract: Zygomycetes are filamentous fungi with a worldwide distribution. This class of fungi encompasses two orders, i.e. the Mucorales and the Entomophthorales. Members of the latter are associated with chronic cutaneous and subcutaneous infections that are limited to the tropics and rarely disseminate to internal organs. The order Mucorales includes several species involved in rhinocerebral, pulmonary, cutaneous, gastrointestinal and other less frequent infections in immunocompetent and immunocompromised individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
111
0
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(121 citation statements)
references
References 73 publications
2
111
0
8
Order By: Relevance
“…Rhinocerebral zygomycosis is characterized by nasal and paranasal sinus involvement as well as orbital, cavernous sinus, and cerebral involvement (9). In our study, the rhinocerebral form (including the rhino-orbital form) was identified in 10 patients, 7 of whom died.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Rhinocerebral zygomycosis is characterized by nasal and paranasal sinus involvement as well as orbital, cavernous sinus, and cerebral involvement (9). In our study, the rhinocerebral form (including the rhino-orbital form) was identified in 10 patients, 7 of whom died.…”
Section: Discussionmentioning
confidence: 79%
“…Diagnosis of zygomycosis was made in accordance with the criteria issued by European Organization for Research and Treatment of Cancer/Mycoses Study Group (13). The clinical forms of zygomycosis have been defined based on the involved organ: rhinocerebral (rhino-orbito-cerebral, rhino-orbital), cutaneous, pulmonary, gastrointestinal, and disseminated (3,9). As well as the clinical findings, radiological imaging methods (computed tomography and magnetic resonance imaging) and endoscopic methods (rhinoscopy, gastrointestinal endoscopy) were used to detect the localization of the infections.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The common risk groups include those on therapeutic interventions corticosteroid therapy, solid tumors and solid organ transplant recipients, acquired or congenital neutropenic patients, those with hematologic disorders and hematopoietic stem cell transplant recipients. In last decades, a link has been reported between infection with the Rhizopus species and resistant gram-negative bacteria which can produce endosymbiotic toxin [4,5]. Hemodialysis patients under treatment with deferoxamine, due to high concentration of free iron in plasma and tissues are at risk for mucormycosis [6].…”
Section: Introductionmentioning
confidence: 99%
“…The presentation type of this infection usually depends on the underlying host conditions [4]. Hyperglycemia and low pH in diabetic patients are the most important risk factors.…”
Section: Introductionmentioning
confidence: 99%